SOOTHER TRIAL: Observational study of an over-the-counter ointment to heal anal itch - Felemovicius, Isaac; Ganz, Robert A.; Saremi, Mohammad; Christopfel, William (Frontiers in Medicine, 2022)
Abstract Introduction: Pruritus ani, or rectal or anal itch, is a common perianal disorder that affects approximately five percent of the population of the developed world. Treatments for this disorder are somewhat limited and include conservative nonmedical perianal hygiene care, and topical medical treatments including topical steroids, antibacterial and antifungal agents, and topical anesthetic/analgesics such as lidocaine or capsaicin; astringents and vasoconstrictors such as ephedrine can also be used. Methods: The study was IRB approved. We assessed the efficacy of a novel, composite, over-the-counter, topical lidocaine ointment that included an epidermal barrier and antimicrobial effect along with the typical lidocaine anesthetizing effect, in a single arm, observational, longitudinal, population of 20 ambulatory pruritus ani patients. Patients applied the ointment twice daily, and were studied for 2 weeks; primary outcomes included time to symptom resolution and clinical exam resolution as measured on a 5-point visual analog scale. Results: Twenty-nine consecutive patients were screened and 20 patients (12 males; 8 females) were enrolled in the study. Ninety percent of patients achieved 100% symptom resolution by 2 weeks, and most were improved within 72 hours of initiating treatment; 95% of patients had a normal visual exam by the 2 week endpoint. There were no significant adverse events attributable to the therapy. Conclusion: Use of a novel composite topical lidocaine agent, demonstrated rapid and effective relief of pruritus ani in an ambulatory population. Additional studies are underway. Registered at Clinicaltrials.gov NCT05288907